Design and Evaluation of Transmitting Antennas for Solar Power Satellite Systems - Alogla, A.; Eleiwa, M. A. H.; Alshortan, H. (Engineering, Technology & Applied Science Research, 2021)
This study attempts to identify, design, and evaluate transmitting antennas for Solar Power Satellite (SPS) systems. The design approach aimed at meeting the SPS operational requirements at ISM bands, namely 2.4-2.5GHz for the NASA and 5.725-5.875GHz for the JAXA models. The primary attributes of SPS antennas for transmitting Beamed High-Power Microwaves (BHPMs) are high power handling capability, efficiency, and directivity with narrow beamwidth and lower sidelobe levels. Using a planar end-fed 20×20 SWA module, the whole planar Slotted Waveguide Antenna Arrays (SWAAs) were designed for both the NASA and JAXA reference models having 1km diameter antenna aperture, peak power level over 1GW, directivity over 80dBi, Side Lobe Level (SLL) less than 20dB, and pencil beam with HPBW less than 0.01°. The proposed slotted waveguide transmitting antenna arrays fulfilled the operational requirements for both the NASA and JAXA SPS reference models. Due to the higher operating frequency, the results showed that the proposed planar SWA array performs better on the JAXA than on the NASA SPS model.